Can neutrophil/lymphocyte ratio and mean platelet volume values be used as early markers in assessing the prognosis of patients with aneurysmal subarachnoid hemorrhage? (Indian Journal of Experimental Biology (IJEB), 2023)
Inflammation plays an important role in cerebrovascular diseases, including intracerebral hemorrhage. Assessing theprognosis of such hemorrgage at early stage adds significance to treatment outcome. In this study, for the first time, we usedneutrophil/lymphocyte (N/L) ratio and mean platelet volume (MPV) values as early markers in assessing the prognosis ofpatients with aneurysmal subarachnoid hemorrhage (SAH). This retrospective study included 50 patients with aneurysmalSAH who were diagnosed, hospitalized, treated, and follow-up with angiography between 2015 and 2016 (Gr. I). Bloodcount parameters and their clinical status after application (the first-arrival Glasgow coma score [GCS]) and at discharge(Glasgow outcome score [GOS]) were examined. The MPV value and N/L ratio were compared with that of thenonaneurysmatic control group (group 2, n = 50). The N/L ratio of Gr. I (median: 10.80) was significantly higher than that ofthe control group (median: 2.20) (P